A cross-sectional study to assess prevalence and factors associated with mild cognitive impairment among older adults in an urban area of Kerala, South India. Issue 3 (20th March 2019) - Mohan, Devi; Iype, Thomas; Varghese, Sara; Usha, Anuja; Mohan, Minu
Abstract : Objectives: To assess the prevalence and factors associated with mild cognitive impairment (MCI) among older adults in an urban area of South India. Setting: The study was conducted in the capital city of Thiruvananthapuram in the South Indian state of Kerala. Participants: The study participants were community-dwelling individuals aged 60 years and above. Primary outcome measure: MCI was the primary outcome measure and was defined using the criteria by European Alzheimer's Disease Consortium. Cognitive assessment was done using the Malayalam version of Addenbrooke's Cognitive Examination tool. Data were also collected on sociodemographic variables, self-reported comorbidities like hypertension and diabetes, lifestyle factors, depression, anxiety and activities of daily living. Results: The prevalence of MCI was found to be 26.06% (95% CI of 22.12 to 30.43). History of imbalance on walking (adjusted OR 2.75; 95 % CI of 1.46 to 5.17), presence of depression (adjusted OR 2.17, 95 % CI of 1.21 to 3.89), anxiety (adjusted OR 2.22; 95 % CI of 1.21 to 4.05) and alcohol use (adjusted OR 1.99; 95 % CI of 1.02 to 3.86) were positively associated with MCI while leisure activities at home (adjusted OR 0.33; 95 % CI of 0.11 to 0.95) were negatively associated. Conclusion: The prevalence of MCI is high in Kerala. It is important that the health system and the government take up urgent measures to tackle this emerging public health issue.